132 A Novel Mechanism of Periventricular Strain Observed in Post-Mortem Human Brains for Mild Traumatic Brain Injury. (April 2023) - Poon, Katherine; Post, Andrew; Brien, Susan; Rovt, Jennifer; Dutrisac, Scott; Cusimano, Michael; Jalali, Alireza; Goodwin, Shannon; Petel, Oren; Karton, Clara; Hoshizaki, Thomas
Abstract : INTRODUCTION: Mild traumatic brain injury (mTBI) can result in a myriad of long-term functional deficits reflecting diffuse axonal disruption. While microstructural anomalies in the periventricular regions of the brain have been identified through immunohistochemical analyses, diffusion tensor imaging and animal models, and contribute to a range of symptoms observed in mTBI, the mechanism of injury is not fully described. METHODS: Post-mortem human brains without space-occupying lesions and significant atrophy were included in this study. Using MRI and anatomical surface landmark localisation, cortical and subcortical markers were implanted along a sagittal plane in anterior, posterior and inferior periventricular regions as well as in the frontal, parietal, occipital and cerebellar lobes. A high-speed, high-resolution, two-dimensional imaging system was employed to measure brain displacement from direct low-velocity frontal impacts. Impact kinematics of the skull were measured using a DTS 6DX SLICE sensor array. Marker displacement in the anterior, inferior and posterior periventricular regions were calculated and individual frame position time-histories for markers' centre of gravity were recorded. RESULTS: Upon impact, the frontal horns of the lateral ventricles were observed to immediately collapse, followed by posterior fluid motion and occipital horn dilation not previously described in the literature. Substantial deformation was recorded in the periventricular areas, resulting in a significantly higher magnitude of strain relative to more superficial subcortical and cortical structures. In comparison, the posterior periventricular region of the brain recorded the highest magnitude of strain. CONCLUSIONS: This study describes the generation of unique high magnitude strain in the periventricular regions from ventricular fluid flow upon low-velocity frontal head impacts. While the clinical significance of the ventricular deformation remains to be elucidated, this represents an important association between the mechanism of injury and diffuse symptomatology observed in mTBI.